(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article deals with sensoriality as an attribute of the scenic and architectural spaces where the plays Vestido de Noiva, Roda Viva and Trate-me Leão took place, which were staged in Rio de Janeiro at the Theatro Municipal in 1943, at Teatro Princesa Isabel in 1943. 1968, and at Teatro Dulcina in 1977, respectively. We present the way in which “sensoriality” promoted the breaking of the “fourth wall”, seeking to demonstrate that this situation provided spectators with an exceptional immersive experience that became of historical interest. We emphasize that the theaters where the three plays premiered have Italian-style stages; Furthermore, we emphasize that, in those dictatorial times, the aforementioned productions of Roda Viva and Trate-me Leão were censored and the actors were victims of violence and aggression.